A novel gait analysis system for detecting abnormal hemiparetic gait patterns during robot-assisted gait training: A criterion validity study among healthy adults - Imoto, Daisuke; Hirano, Satoshi; Mukaino, Masahiko; Saitoh, Eiichi; Otaka, Yohei (Frontiers in Neurorobotics, 2022)
Introduction: Robot-assisted gait training has been reported to improve gait in individuals with hemiparetic stroke. Ideally, the gait training program should be customized based on individuals’ gait characteristics and longitudinal changes. However, a gait robot that uses gait characteristics to provide individually tailored gait training has not been proposed. The new gait training robot, “Welwalk WW-2000,” permits modification of various parameters, such as time and load of mechanical assistance for a patient’s paralyzed leg. The robot is equipped with sensors and a markerless motion capture system to detect abnormal hemiparetic gait patterns during robot-assisted gait training. Thus, it can provide individually tailored gait training. This study aimed to investigate the criterion validity of the gait analysis system in the Welwalk WW-2000 in healthy adults. Methods: Twelve healthy participants simulated nine abnormal gait patterns that were often manifested in individuals with hemiparetic stroke while wearing the robot. Each participant was instructed to perform a total of 36 gait trials, with four levels of severity for each abnormal walking pattern. Fifteen strides for each gait trial were recorded using the markerless motion capture system in the Welwalk WW-2000 and a marker-based three-dimensional motion analysis system. The abnormal gait pattern index was then calculated for each stride from both systems. The correlation of the index values between the two methods was evaluated using Spearman’s rank correlation coefficients for each gait pattern in each participant. Results: Using the participants’ index values for each abnormal gait pattern obtained using the two motion analysis methods, the median Spearman’s rank correlation coefficients ranged from 0.68 to 0.93, which corresponded to moderate to very high correlation. Conclusions: The gait analysis system in the Welwalk WW-2000 for real-time detection of abnormal gait patterns during robot-assisted gait training was suggested to be a valid method for assessing gait characteristics in individuals with hemiparetic stroke. Trial registration: This study was registered in the Japan Registry for Clinical Trials (https://jrct.niph.go.jp; jRCT 042190109) on January 22, 2020.